Improving stability of organometallic-halide perovskite solar cells using exfoliation two-dimensional molybdenum chalcogenides - Nicolosi, Valeria; Sanvito, Stefano (My University, 2020)
Organometallic-halide perovskite solar cells (PSCs) are emerging as the most promising next generation solar cell devices. However, the stability is still the main bottleneck of their further development. Here, we introduce two-dimensional (2D) molybdenum chalcogenides (MoS 2 and MoSe 2 ) (MCs) nanoflakes as a buffer layer between perovskite layer and hole transport layer (HTL) to improve the stability of the organometallic-halide PSCs. 2D MCs are obtained via liquid-phase exfoliated (LPE) approach, and Glass/FTO/compact-TiO 2 / mesoporous-TiO 2 /FA 85 MA 15 PbI 85 Br 15 /2D MCs/Spiro-OMeTAD/Au structured solar cell devices are designed and fabricated. In this system, 2D MCs act both as a protective layer and an additional HTL of PSCs. This kind of PSCs achieve a relatively high-power conversion efficiency (PCE) of 14.9%, along with a much longer lifetime stability compared to the standard PSCs. After 1 h, PCE of the PSC adding a 2D MCs buffer layer could maintain 93.1% of initial value, while the PCE of the standard PSC dropped dramatically to 78.2% of initial efficiency. Our results pave the way towards the implementation of 2D MCs nanoflakes as a material able to boost the shelf life of PSCs and further provide the opportunity to fabricate large-area PSCs in view of their commercialization.
PUBLISHED
cited By 0
Keywords: commercialization; Organometallic-halide perovskite solar cells (PSCs); next generation solar cell devices.; commercialization; Organometallic-halide perovskite solar cells (PSCs); next generation solar cell devices.